Hubungan Tingkat Pengetahuan dan Sikap dengan Praktik Personal Hygiene Penjamah Makanan di Cafe Proof.Co Mojokerto - Shavira Nursifa; Choirul Anna Nur Afifah; Sri Handajani; Ita Fatkhur Romadhoni (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Personal hygiene in food handlers is the key to success in safe and healthy food processing. One of the factors that affect the personal hygiene practices of food handlers is the level of knowledge and attitude. This study aims to determine the relationship between the level of knowledge and attitudes and the practice of personal hygiene of food handlers in cafes Proof.co Mojokerto. This study is a quantitative research using a cross-sectional approach. The respondents in this study were 9 people. Data were collected using knowledge instruments, attitude questionnaires and observation sheets. The data analysis used was a spearman rank correlation test to determine the relationship between knowledge level and attitude with the personal hygiene practices of food handlers. The results of this study showed that there was a relationship between knowledge level (p-value 0,005) and personal hygiene practices and no relationship between attitude (p-value 0,075) and personal hygiene practices. The conclusion of this study is that there is a relationship between the level of knowledge and the practice of personal hygiene and there is no relationship between attitude and the practice of personal hygiene of food handlers at Cafe Proof.co Mojokerto.